A new Ostrowski type inequality for functions whose first derivatives are of bounded variation - Budak Hüseyin; Sarikaya Mehmet Zeki (Moroccan Journal of Pure and Applied Analysis, 2016)
In this paper, we establish some new Ostrowski type integral inequalities for mappings whose first derivatives are of bounded variation and quadrature formula is provided